Mindfulness-based group intervention for an adolescent girl at risk for type 2 diabetes: a case study - Dalager, Stephanie, author; Shomaker, Lauren, advisor; Coatsworth, Doug, committee member; Schmid, Arlene, committee member (Colorado State University. Libraries, 2017)
Adolescent-onset type 2 diabetes (T2D) is a rising healthcare problem that disproportionately impacts females and historically disadvantaged racial/ethnic groups. Standard behavioral lifestyle interventions to prevent T2D by lowering body mass index (BMI) to lessen insulin resistance, a key precursor to T2D, unfortunately have had limited long-term success. Underlying psychosocial factors, particularly depressive symptoms, have been related to insulin resistance and T2D, independent of BMI. Mindfulness-based group interventions are being utilized increasingly in adults with T2D to address depression. More recently, using a prevention lens, mindfulness-based programs have shown preliminary promise for intervening with elevated depressive symptoms and insulin resistance in adolescents at risk for T2D. Yet given the newness of this area, little research exists to deepen understanding around clinical implementation and acceptability with this at-risk, adolescent population. In the current case study, we present the experience of an adolescent girl with elevated depressive symptoms, obesity, insulin resistance, and a family history of T2D, who participated in a six-week mindfulness-based group program delivered at an outpatient therapy clinic in the context of a pilot clinical research study. At baseline, immediately following the group program, and at one-year follow-up, surveys and interviews were administered to evaluate mindfulness and depression; hypothalamic-pituitary-adrenal axis activity; BMI and body fat were assessed; and insulin resistance was estimated from the homeostasis model assessment of insulin resistance (HOMA-IR). Case results indicated increased dispositional mindfulness, decreases in depressive symptoms, and lessening of insulin resistance. BMI and body fat were stable. Key therapeutic themes that emerged for the participant included increased recognition of internal experience and decreased reactivity to stress, which might help to explain the positive psychological and insulin outcomes. We discuss several implications of the case study for potentially increasing the success of implementing mindfulness-based programs in this population, including more emphasis on the promotion of social connections among group members, increasing adherence to home practice, and facilitation techniques to promote concrete understanding of abstract mindfulness concepts. The current case results suggest that teaching mindfulness skills to adolescent girls at risk for T2D with depressive symptoms possibly may offer benefits for depression and T2D risk. Adequately-powered clinical trial data are required to evaluate these results on a larger scale.